2000
DOI: 10.2307/2641291
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Presence and Abundance of a Small Mammal Species: The Effect of Scale and Resolution

Abstract: Management of small mammal communities in forest ecosystems requires a working knowledge of the scales at which species presence and abundance can best be predicted. Habitat-based models were developed to characterize the distribution of a boreal relict, the southern red-backed vole, Clethrionomys gapperi, in the southern Appalachian Mountains, USA, at three hierarchical scales of analysis. Vole presence and abundance were most evident at the high-resolution (macrohabitat) scale, followed by the intermediatere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 40 publications
2
42
0
1
Order By: Relevance
“…For example, similar landscape and habitat effects (e.g. Andrews and O'Brien 2000;Orrock et al 2000;Panzacchi et al 2010) and negative interspecific interactions (e.g. Fox and Fox 2000;Eccard and Ylonen 2003;Morris 2005) have been revealed in well established small mammal communities.…”
Section: Discussionmentioning
confidence: 98%
“…For example, similar landscape and habitat effects (e.g. Andrews and O'Brien 2000;Orrock et al 2000;Panzacchi et al 2010) and negative interspecific interactions (e.g. Fox and Fox 2000;Eccard and Ylonen 2003;Morris 2005) have been revealed in well established small mammal communities.…”
Section: Discussionmentioning
confidence: 98%
“…However, the variables we considered and the way that they were measured could be masking the importance of vegetation cover on rabbit population change. Furthermore, another important issue to consider in studies of the influence of vegetation cover is the role of scale (Orrock et al 2000). Silva et al (2005) suggested that microhabitat characteristics tend to influence small mammals at the population level while macrohabitat and landscape features are important determinants of small mammals especially at the community level.…”
Section: Habitatmentioning
confidence: 99%
“…1b-d, where D is replaced by the percent difference in browse availability between cut and uncut stands), which represents their main source of food during winter (Pease et al 1979). Red-backed voles have high water requirements (Getz 1968) and are most commonly associated with mesic forest habitats with moist microclimates provided by coarse woody debris, shrubs and moss cover (Morris 1996;Orrock et al 2000). We therefore tested additional isodar models for voles that included moss cover as a measure of microhabitat moisture (i.e., scenarios in Fig.…”
Section: Introductionmentioning
confidence: 99%